The Impact of Investment and Labor Force Participation on Poverty in Aceh: The Mediating Role of Per Capita Income - Wayus, Dicky; Safuridar, Safuridar; Syarief, Salman (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2025)
Research Originality: Poverty remains a persistent challenge in Aceh Province despite multiple interventions. This study contributes to the literature by examining both the direct and indirect effects of investment and labor on poverty, as measured by per capita income, using path analysis. Research Objectives: The study aims to examine the impact of Labor Force Participation Rate (LFPR), Domestic Investment (DI), and Foreign Direct Investment (FDI) on poverty, with per capita income (PCI) as a mediating factor. Research Methods: Time-series data from 2009 to 2023 were analyzed using path analysis to identify direct and indirect relationships. Empirical Results: Findings show that per capita income has the most substantial effect in reducing poverty. DI significantly influences poverty, both directly and indirectly, while LFPR and FDI exhibit no significant impact; however, both trends show a negative correlation with poverty. Implications: Poverty alleviation strategies should prioritize income growth through domestic investment optimization and enhancing workforce quality. JEL Classification: I32, I21, F21, O16 How to Cite:Wayus, D., Safuridar., & Syarief S. (2025). The Impact of Investment and Labor Force Participation on Poverty in Aceh: The Mediating Role of Per Capita Income. Signifikan: Jurnal Ilmu Ekonomi, 14(2), 505-520. https://doi.org/10.15408/sjie.v14i2.46434.